How exaptation mediates the effects of customer participation on low-cost innovation: The role of strategic flexibility - Tang, Chaoyong; Shi, Yongzhi; Zhu, Xuechun; Li, Yibo (Frontiers in Psychology, 2022)
With the advent of emerging markets, the need for low-cost innovation to meet the rising demands of people at the base of the pyramid has increased significantly. Although the critical influence of customer participation on new product development has been recognized, there have been few studies on the effects of customer participation on low-cost innovation. This study builds a moderated mediation model and explores the roles of customer participation on low-cost innovation. Based on the exaptation and strategic flexibility theories, the mediating role of exaptation and the moderating role of strategic flexibility are emphasized. A survey of 348 firms revealed that customer participation positively impacted both exaptation and low-cost innovation. In addition, exaptation mediated the correlation between customer participation and low-cost innovation. Resource flexibility negatively moderated the correlation between customer participation and exaptation and negatively moderated the mediating effect of exaptation. Furthermore, coordinate flexibility positively moderated the correlation between customer participation and exaptation and positively moderated the mediating effect of exaptation.